Is there a protective effect with remote ischemic preconditioning on contrast-induced acute renal injury after coronary angiography in low-risk patients? - Sanaz Soleymani; Hamid Reza Samimagham; Mohammad Tamaddondar; Hossein Farshidi; Mahmood Khayatian; Azadeh Moradkhani (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: Contrast-induced acute kidney injury (CIN-AKI) is a serious complication of coronary angiography. Given the weaknesses in the common protective methods used to prevent CIN-AKI, a safe and effective strategy is needed. RIPC has been shown to have a nephroprotective effect. Objectives: We aimed to determine the protective effect of RIPC on CIN-AKI after angiography or percutaneous coronary intervention (PCI) in low-risk patients. Patients and Methods: In our study, 140 low-risk patients who needed angiography or PCI, were assigned to either RIPC or control group. In each group, serum creatinine and urinary neutrophil gelatinaseassociated lipocalin (uNGAL) were measured before the procedure. Serum creatinine was measured daily for 2 days and uNGAL was measured 6 and 24 hours after the procedure. Diagnosis of AKI was, according to the Kidney Disease; Improving Global Outcomes (KDIGO) criteria (2012). Results: The mean age in the remote ischemic preconditioning (RIPC) group was 56.8 ± 11.4 years and 56.3 ± 11.8 years in the control group. We observed no significant difference regarding patient's characteristic and renal biomarkers at baseline. There was no significant difference in the incidence of AKI (P = 0.116). The uNGAL increased by 36.2% 6-hour after the procedure in patients with AKI, while at the same time, this biomarker increased only by 4.3% in patients without AKI. Conclusion: We concluded that RIPC, with 3 cycles of 5-minute ischemia and 5-minute reperfusion, did not decrease CIN-AKI or altering renal biomarkers course in low-risk patients undergoing coronary angiography or PCI. Additionally, uNGAL, seems to be an appropriate biomarker for early diagnosis of CIN-AKI, 6 hours after contrast media exposure.